Assessment of gadgets addiction and its impact on health among undergraduates - Kumar, Aravind K.; Sherkhane, Mayur S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Technology has made our youth the most vulnerable group among today’s population, because of their accessibility and addiction to newer gadgets, which are cheap and easily available. Society has always been worrying about the term ‘Drug Addiction’ of our youth but ‘Gadget Addiction’ is a more critical area of concern in the present era and is a threat to the social infrastructure in the future. Addiction is an irrepressible urge which is accompanied by loss of control leading to lower emotional intelligence indirectly deteriorating the academic and professional performance as well as hampering their family life leading to life threatening problems in future. Methods: Cross sectional study was done among 200 undergraduates using predesigned and pretested questionnaire. Gadget dependency was analysed using 5-point Likert-scale. Descriptive statistics and chi-square test was used for analysing the data collected. Results: 71% belonged to 21-24 years age group. 73.5% were males and 43.5% belonged to class I socio-economic status and 70% had normal BMI. 72.5% of subjects had first gadget at 16-20 years and 90.5% were using smart-phones as a common gadget, of them, 50.2% were using for more than 7 hours a day. 61% had difficulty in day to day work performance. Females were more prone compared to males (p=0.008). Conclusions: High level of dependency was present with gadget addiction. Health action to be taken in form of counselling about the pros and cons in the early phase can prevent future complications.